Pengaruh Dosis Pupuk Organik Cair FloraOne® Terhadap Pertumbuhan Tanaman Tomat (Solanum lycopersicum L.) - Hoki Masriono Manik; Azwir Anhar (Universitas Cokroaminoto Palopo, 2026)
Tomato plants (Solanum lycopersicum L.) are horticultural commodities that have high nutritional value and economic value and are widely needed by the community. The increase in demand for tomatoes needs to be balanced with efforts to increase production through proper cultivation techniques, one of which is through fertilization. The continuous use of inorganic fertilizers can reduce soil fertility and negatively impact the environment, so a more environmentally friendly fertilization alternative, such as the use of liquid organic fertilizer (POC), is needed. FloraOne® liquid organic fertilizer contains nutrients and microorganisms that have the potential to support plant growth. This study aims to determine the effect of applying FloraOne® liquid organic fertilizer on the growth of tomato plants. The research was carried out using an experimental method with a Complete Random Design (RAL) consisting of seven FloraOne® concentration treatments, namely P0 (control), P1 (0.1%), P2 (0.2%), P3 (0.3%), P4 (0.4%), P5 (0.5%), and P6 (0.6%) with four replicates. The observed parameters included plant height, stem diameter, wet weight, dry weight, and flowering age. The data was analyzed using the Analysis of Variance (ANOVA) test at a significance level of 5%. The results showed that the application of FloraOne® liquid organic fertilizer did not have a significant effect on the height, diameter, wet and dry weight of tomato plants (p>0.05) while P3 and P6 showed the appearance of flowers in the 8th week. However, descriptively, the 0.3% concentration treatment showed a better growth tendency than the other treatments.